2017
DOI: 10.1080/13880209.2017.1285325
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic evaluation of the traditional uses of Nepeta ruderalis in gastrointestinal and airway disorders

Abstract: Context:Nepeta ruderalis Buch.-Ham. (Lamiaceae), locally known as Badranj Boya, is an aromatic herb used traditionally as an antispasmodic, antidiarrhoeal, and anti-asthamatic remedy.Objective: Aqueous methanolic extract of N. ruderalis was studied to investigate its traditional uses.Materials and methods: Study was conducted from September 2015 to February 2016. In vitro spasmolytic and broncho-relaxant activity of crude extract of N. ruderalis (whole plant) was evaluated at 0.01–10 mg/mL final bath concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Decoctions and infusions from the aerial parts of Nepeta species have been used in traditional and folk medicines as antioxidant, anticonvulsant, tonic, antipyretic, antitussive, sedative, antiasthmatic, antispasmodic and anti-inflammatory medicines [4,5]. Some of these therapeutic actions were recently comprehensively reviewed [6] and received a modern pharmacological validation [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Decoctions and infusions from the aerial parts of Nepeta species have been used in traditional and folk medicines as antioxidant, anticonvulsant, tonic, antipyretic, antitussive, sedative, antiasthmatic, antispasmodic and anti-inflammatory medicines [4,5]. Some of these therapeutic actions were recently comprehensively reviewed [6] and received a modern pharmacological validation [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The above conclusions demonstrate the safety of EWOV and provide necessary theoretical basis for subsequent experiments. Castor oil is from castor seed and is a kind of effective laxative, which can reduce the absorption of small intestine and increase the secretion of it [24]. The active ingredient of castor oil inducing diarrhea is ricinoleic acid, which produces irritating and in ammatory actions on the intestinal mucosa and leads to the release of prostaglandins [25].…”
Section: Discussionmentioning
confidence: 99%
“…N. flavida and N. sintenisii revealed antioxidant capacity in two previous in vitro studies (Shakeri et al, ; Tepe et al, ). Anticonvulsant and myorelaxant activity researches on N. sibthorpii , N. cataria , and N. ruderalis have shown that these three species possess anticonvulsant and myorelaxant effects (Galati et al, ; Gilani et al, ; Mahmood et al, ). N. menthoides attenuated the development of morphine dependence and potentiated morphine analgesia (Rahmati & Beik, ).…”
Section: Biological Activity Studies On Nepeta L Genusmentioning
confidence: 99%
“…Mice did not show acute toxicity at doses up to 5 g/kg. Broncho-relaxant and spasmolytic effects were mediated by calcium channel blocking activity caused by rightward displacement of higher concentrations of concentration-response curves of calcium(Mahmood, Chaudhry, Masood, Saeed, & Adnan, 2017).…”
mentioning
confidence: 99%